Methods of Isolation of Active Substances from Garlic (Allium sativum L.) and Its Impact on the Composition and Biological Properties of Garlic Extracts - Monika Bar; Urszula E. Binduga; Konrad A. Szychowski (MDPI AG, 2022)
Garlic (Allium sativum L.) is widely used in the human diet and in scientific research due to its biological properties. Various factors, e.g., temperature, pressure, extraction method, type of solvent, size, and territorial origin of garlic, affect the amount and type of bioactive compounds obtained from garlic extracts. In turn, the content of bioactive compounds correlates with the biological activity of the extracts. Therefore, the aim of this review was to summarize the current state of knowledge of the methods and effectiveness of isolation of active substances from garlic and their impact on the garlic extract composition and, consequently, biological properties. According to the literature, extracts obtained using water as a solvent are mainly responsible for antimicrobial properties, which is related to, inter alia, the high content of allicin. The use of alcohols, such as methanol or ethanol, is associated with the outstanding antioxidant power of extracts resulting from the presence of phenolic compounds. In turn, due to the presence of diallyl disulfide and disulfide trisulfide, garlic oil has anticancer potential. Acetone is the most effective organic solvent; however, it is not suitable for immediate consumption.